Desentralisasi Fiskal dan Tingkat Kemandirian Daerah(Studi Pada Kabupaten Dan Kota Di Provinsi Jawa Barat) - Pupung Puad Hasan (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2014)
Fiscal decentralization is a form of delegated authority of the central government to local governments in matters of financial management. Local governments are given the authority to explore potential sources of local revenue in accordance with applicable regulations. Submission sources of revenue for local governments in the region should ideally be able to encourage selffinance its expenditure. Minimum local governments are able to finance expenditures of local government employee nevertheless remains dependent on central government transfers, it is shown by the local government is still dependent on the balance of funds by the central government through the DAU, DAK and other legal equalization funds. This study aims to determine the level of regional dependency on the central government decentralization era during his journey in the past 10 years (2001-2011). The sample in this study are some regencies/districts and cities in the Province of West Java. The results showed that the degree of independence of local government is still low, which means dependence on the central government is still high. Some areas even shows for local income can not afford to finance recurrent expenditure.